A Spectre is Haunting the World - the Spectre of Global Capitalism - KINGSTON, WILLIAM (Springer-Verlag, 2000)
Individual property rights are fruitful for economic development because they civilize self-interest by forcing it to serve the public good. Globalization represents individual property rights that are out of control, since there is no global mechanism for civilizing self interest. Schumpeter's sense of the impending demise of capitalism, if not of its replacement by socialism, may yet be vindicated.
PUBLISHED
Keywords: Globalization; Property rights; World Trade Organization; Schumpeter